Impact of Gender and Technological Innovation on Energy Efficiency - Türüç, Fatma; Ayantayo, Rukayat Olaide (New Energy Exploitation and Application, 2024)
This study investigates how men and women in MINT countries contribute to enhancing energy efficiency across various sectors through technological innovation. Gender plays a pivotal role in the energy efficiency landscape, and this study examines how promoting gender equality and increasing women's participation in innovation can enhance energy efficiency outcomes. Using data from the World Bank and an annual panel dataset of MINT nations from 1997 to 2020, this study analyzes the relationship between energy efficiency and variables such as per capita consumption of renewable energy, GDP, gender, and urbanization. The study uses the panel autoregressive distributed lag (ARDL) model to examine the variables' long- and short-term relationships. The panel ARDL method has two steps: first, testing for the presence of a long-term relationship between the components, and then, using those results, calculating the long-term coefficients. The study used a causality evaluation which considers the potential causal association between the regressors and the dependent series to determine the presence and direction of causal relationships between the two data sets. If a cointegrating link can be established, it suggests that there may be a causal connection between the indicators, while the direction of causation remains unknown. This research provides empirical evidence of the complex interplay between gender, technological innovation, and energy efficiency in MINT countries. It highlights that gender-sensitive policies and renewable energy sources are crucial to the success of international efforts to promote sustainable development.